Diagnosis of voices disorders using MEL scaled WPT and functional link neural network - Paulraj, Muregesa Pandiyan, Prof. Madya Dr.; Sazali, Yaacob, Prof. Dr.; Hariharan, Muthusamy (Biomedical Fuzzy Systems Association (BMFSA), 2011)
Link to publisher's homepage at http://www.f.waseda.jp/